2021
DOI: 10.1128/msphere.00084-21
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Effects on the Delivery Efficacy of Bifidobacterium animalis subsp. lactis BB-12 on Fecal Microbiota, Gut Transit Time, and Short-Chain Fatty Acids in Healthy Young Adults

Abstract: Bifidobacterium animalis subsp. lactis BB-12 is a probiotic strain that has been used worldwide since 1985. It has commonly been delivered in fermented dairy products for perceived benefits associated with gut health and enhanced immune function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 76 publications
(90 reference statements)
0
6
0
1
Order By: Relevance
“…This could suggest a potential mechanism of action. A recent study was, however, not able to replicate the effect on intestinal transit time ( 115 ); most likely because of the small number of subjects and that subjects were not selected to have long transit times or be constipated. Consumption of yogurt or a capsule with the strain was not found to change the intestinal microbiota, this is not unusual; the resilience of a healthy colonic microbiota is likely to resist change from one (probiotic) strain ( 116 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could suggest a potential mechanism of action. A recent study was, however, not able to replicate the effect on intestinal transit time ( 115 ); most likely because of the small number of subjects and that subjects were not selected to have long transit times or be constipated. Consumption of yogurt or a capsule with the strain was not found to change the intestinal microbiota, this is not unusual; the resilience of a healthy colonic microbiota is likely to resist change from one (probiotic) strain ( 116 ).…”
Section: Discussionmentioning
confidence: 99%
“…Consumption of yogurt or a capsule with the strain was not found to change the intestinal microbiota, this is not unusual; the resilience of a healthy colonic microbiota is likely to resist change from one (probiotic) strain ( 116 ). However, consumption of the probiotic yogurt did lead to fecal recovery of the strain ( 115 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that probiotics can use prebiotics as carbon and energy sources through glycoside hydrolases (GHs). 21,22 CAZy analysis with whole genome sequencing revealed that L. reuteri C501 contains endo-inulinase (EC 3.2.1.7) and exo-inulinase (EC 3.2.1.80), and the glycoside hydrolases of GH32 were involved in the hydrolysis of prebiotic inulin; and L. reuteri C501 was found to use exo-beta-1,3-glucanase (EC 3.2.1.58) and endo-beta-1,3-glucanase (EC 3.2.1.39) of GH55, and endo-1,3(4)-beta-glucanase (EC 3.2.1.6) glycoside hydrolases of GH16 to hydrolyze the prebiotic β-glucan.…”
Section: Resultsmentioning
confidence: 99%
“…lactis BB-12 and L. acidophilus LA-5 ( 81 ) or B. animalis subsp. lactis BB-12 isolated ( 82 ), the use of cheese as a probiotic matrix was shown to be less effective in the adhesion of the probiotic strain to the GI tract ( 83 ). Thus, further RCTs are needed to assess whether there is a difference between probiotic matrices and whether there is a difference between the content where the probiotic capsules or sachets will be dissolved for consumption.…”
Section: Resultsmentioning
confidence: 99%